Modified Scaffolds With Magnetic Nanoparticles in Periodontal Tissue Regeneration - Dulce Araceli Guzman‐Rocha; Benjamin Aranda‐Herrera; Laura Susana Acosta Torres; Ma. Concepción Arenas‐Arrocena; Rene Garcia‐Contreras (Nano Select)
ABSTRACT Nanomaterials have displayed vast potential across a spectrum of biomedical applications, particularly in recent studies aimed at optimizing traditional systems. Metal oxide nanoparticles, like Magnetic nanoparticles (MNPs), offer unique physicochemical properties ideal for biomedical applications, advancing diagnostics, therapies, tissue engineering and imaging technologies in medicine. Their notable features, such as high specific surface area and porous structure, render them versatile for myriad medical and biological uses. When combined with polymers, MNPs have found utility in nano‐scale treatments targeting specific human ailments, encompassing drug delivery, tissue engineering, and wound care. This review focuses on summarizing the utilization of MNPs examining their structural attributes, magnetic properties, biocompatibility, and their role in scaffolding applications. Furthermore, within the dental domain, periodontitis presents substantial challenges, prompting research into regenerative therapies to foster the growth and specialization of key cell types crucial for effective disease management and tissue revitalization.